KOMUNIKASI POLITIK: KAJIAN SUBSTANSIAL DALAM PENDEKATAN POLITIK - Thomas T. Pureklolon (Jurnal Visi Komunikasi, 2021)
Political communication consists of political actors and political messages relating to power, governance, and all government policies. This communication takes place in complex political behavior. The complexity of political communication runs in a political process that is always unique and strategic from a communicator through messages and media. The speaking ability and representation of a communicator are the main determining elements in political communication. Political communication is a dynamic element that can determine political socialization and at the same time determine political participation. In this case political communication can be a pattern of human political behavior and a major determinant in politics. Therefore; Political communication is communication that involves political messages and political actors, or is directly related to power, government and government policies in a country. Political communication can also be understood as communication between two institutions, namely "those who govern" and "those who are ruled." This is an important thing in political communication. In every human activity always requires communication. It can be said that communication is an absolute thing in the concrete life of every human being. Communicators in a communication always occur in a social life matrix. Communication also occurs in social situations from the very beginning of a communication, develops until its end, which means: the relationship between the communicator and the public or the public is an inseparable part of the social system. Mass communicators as organizations that occupy important sensitive positions in social networks, respond to various pressures by rejecting and selecting information that all occur in the relevant social system that develops in society at that time. In a political communication, there are often figures of political communicator figures who certainly have authority and popularity such as community leaders, religious leaders, or celebrities, and so on, which are used effectively to attract the masses, such as in elections to gain votes. Actions like this are perfectly fine in a political communication, including also displaying large-scale advertisements with gleaming and excitement. In political communication, the content of political messages uses the media more than using public communication such as campaigns or speeches. The content of political messages is also directly related to the media setting agenda which always comes from orders from certain groups or groups, in this case a propaganda can also play in the message which aims to form new perceptions in the eyes of the public. This political message can influence the success process of a political party when competing for votes for power. The writing method in this article is a qualitative method, literature study with an interdisciplinary approach.